Improving Student Learning Outcomes in Islamic Religious Education Learning through the Use of Learning Video Media - Yurnita (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve students' learning outcomes in Islamic religious education learning using audio-visual media. This research uses a type of classroom action research. This research design uses the Kemmis & Mctaggart design with four steps, namely planning, action, observation and reflection. The subjects of this research were elementary school students. Data was obtained using test and observation techniques. The data obtained was then analyzed using descriptive statistical techniques. The research results show that audio visual media can improve learning outcomes of students in Islamic religious education learning by implementing audio visual media. This can be seen in the first cycle, the average percentage was 50% and in the second cycle it was 86%. So it can be stated that student activities develop in the second cycle. Improving student learning outcomes through the application of audio-visual media to Islamic religious education material at state elementary school 081228 Sibolga was carried out over two cycles. Learning outcomes in the first cycle were 66.67% and in the second cycle were 76.67%. So it can be stated that student learning outcomes have improved better in the second cycle. Based on this, audio visual media can be used as a medium that can be considered by teachers to overcome the problem of low learning outcomes, especially in learning Islamic religious education.